Common polymorphic deletion of glutathione S‐transferase theta predisposes to acquired aplastic anemia: Independent cohort and meta‐analysis of 609 patients. Issue 10 (23rd July 2013) - Babushok, Daria V.; Li, Yimei; Roth, Jacquelyn J.; Perdigones, Nieves; Cockroft, Joshua D.; Biegel, Jaclyn A.; Mason, Philip J.; Bessler, Monica
<x xml:space="preserve">Abstract</x> Acquired aplastic anemia (AA) is a rare life‐threatening bone marrow failure syndrome, caused by autoimmune destruction of hematopoietic stem and progenitor cells. Epidemiologic studies suggest that environmental exposures and metabolic gene polymorphisms contribute to disease pathogenesis. Several case–control studies linked homozygous deletion of the glutathione S‐transferase theta (GSTT1) gene to AA; however, the role of GSTT1 deletion remains controversial as other studies failed to confirm the association. We asked whether a more precise relationship between the GSTT1 null polymorphism and aplastic anemia could be defined using a meta‐analysis of 609 aplastic anemia patients, including an independent cohort of 67 patients from our institution. We searched PubMed, Embase, and the Cochrane Database for studies evaluating the association between GSTT1 null genotype and development of AA. Seven studies, involving a total of 609 patients and 3, 914 controls, fulfilled the eligibility criteria. Meta‐analysis revealed a significant association of GSTT1 null genotype and AA, with an OR = 1.74 (95% CI 1.31–2.31, P < 0.0001). The effect was not driven by any one individual result, nor was there evidence of significant publication bias. The association between AA and GSTT1 deletion suggests a role of glutathione‐conjugation in AA, possibly through protecting the hematopoietic compartment from endogenous metabolites or environmental exposures. We propose a model whereby protein adducts generated by reactive metabolites serve as neo‐epitopes to trigger autoimmunity in aplastic anemia. Am. J. Hematol. 88:862–867, 2013. © 2013 Wiley Periodicals, Inc.